Historical Memory of Antique Vases: Aspect of Collecting in Lithuania in the 19th Century - Būčys, Žygintas (Bibliotheca Lituana, 2012)
The National Museum of Lithuania owns a small collection of Antique culture items. This article analyzes and identifies the history of three Antique vases from that collection: the ways in which they came to the museum, to whom they belonged, and what was the meaning of Antique in Lithuanian society in the first half of the 19th century. The reconstructed collection of count Adam Günther is compared with other collections of the Lithuanian aristocracy of that time. This article aims to reflect incentives, aspirations of that time collectors’, and their perception of the national country heritage as well as the common European heritage.
Keywords: none